The cellular function and molecular mechanism of formaldehyde in cardiovascular disease and heart development. Issue 12 (10th May 2021) - Zhang, Ying; Yang, Yanyan; He, Xiangqin; Yang, Panyu; Zong, Tingyu; Sun, Pin; Sun, Rui‐cong; Yu, Tao; Jiang, Zhirong
Abstract: As a common air pollutant, formaldehyde is widely present in nature, industrial production and consumer products. Endogenous formaldehyde is mainly produced through the oxidative deamination of methylamine catalysed by semicarbazide‐sensitive amine oxidase (SSAO) and is ubiquitous in human body fluids, tissues and cells. Vascular endothelial cells and smooth muscle cells are rich in this formaldehyde‐producing enzyme and are easily damaged owing to consequent cytotoxicity. Consistent with this, increasing evidence suggests that the cardiovascular system and stages of heart development are also susceptible to the harmful effects of formaldehyde. Exposure to formaldehyde from different sources can induce heart disease such as arrhythmia, myocardial infarction (MI), heart failure (HF) and atherosclerosis (AS). In particular, long‐term exposure to high concentrations of formaldehyde in pregnant women is more likely to affect embryonic development and cause heart malformations than long‐term exposure to low concentrations of formaldehyde. Specifically, the ability of mouse embryos to effect formaldehyde clearance is far lower than that of the rat embryos, more readily allowing its accumulation. Formaldehyde may also exert toxic effects on heart development by inducing oxidative stress and cardiomyocyte apoptosis. This review focuses on the current progress in understanding the influence and underlying mechanisms of formaldehyde on cardiovascular disease and heart development.